Synthesis of S-aryl dithiocarbamates and its in-silico studies - Krishnarao Jayaram Desai; Murugesan Santhosh; Padmanaban Akashvarunan; Ponraj Abarna; Boopathi Shagunthala Hariprasad; Sundaram Ganesh Babu; Annamalai Pratheepkumar (Results in Chemistry)
Environmentally friendly facile synthesis of aryl dithiocarbamates via a one-pot procedure by the reaction between secondary amines and carbon disulphide produced dithiocarbamates, which underwent copper-assisted intermolecular CS cross-coupling with aryl Iodides are developed. Cu2O is employed as a catalyst and water used as a green solvent, owing to their high reaction efficiency and benign reaction conditions in the context of green chemistry. We demonstrated detailed studies of possible intermediates, product diversification, and in-silico properties for some of the novel S-Aryl dithiocarbamates. Further, the compound 3cg possess good binding affinity towards alpha-amylase protein in comparison with Metformin.